Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013 1st International Workshop on Conducting Empirical Studies in Industry (CESI) 2013
DOI: 10.1109/cesi.2013.6618468
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing by similarity: Lessons learnt from industrial case studies

Abstract: Large IT vendors execute thousands of projects in a variety of business domains and environments. Over the years, they end up repeatedly developing and deploying systems for a given domain in the same country, sometimes even for the same company. It would save them a lot of cost and effort if they could reliably depend on their past experience and draw insights from lessons learnt in the past. However, this requires them to generalize from past projects to a similar current project. In this paper we draw lesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Different generalizations will probably need different architectural similarities. Architectural similarity is a worthy research topic that can only be performed in cooperation with practitioners [102,103]. There are some published results about the (dis)similarity between software engineering students and software engineering professionals [104,105,106], but more needs to be done.…”
Section: Discussionmentioning
confidence: 99%
“…Different generalizations will probably need different architectural similarities. Architectural similarity is a worthy research topic that can only be performed in cooperation with practitioners [102,103]. There are some published results about the (dis)similarity between software engineering students and software engineering professionals [104,105,106], but more needs to be done.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the external validity, a threat could be related to the fact that we used only applications from one company. Even if we can image that with a comparable organization, in terms of project size, quality of teams, experience of team members, and application domain, we might expect similar observations, we intend to conduct further studies with data sets from other companies [15].…”
Section: Threats To Validitymentioning
confidence: 98%
“…Ghaisas et al [5] address the related, but wider, question of how to generalize from observations in several similar cases. They argue that case studies have different context attributes and as soon as the attributes of reported cases vary from a newly observed case, the researcher may not be able to predict the outcome of the project.…”
Section: Related Workmentioning
confidence: 99%
“…[12]). Consequently, understanding these relations will help in reasoning about the reasons for success and failure of decisions in the respective contexts when comparing cases (as discussed in the related work by Ghaisas et al [5]). …”
Section: B Relation To Architecture Decision Makingmentioning
confidence: 99%